Switching From Originator Adalimumab to the Biosimilar SB5 in Patients With Inflammatory Bowel Disease: Short-term Experience From a Single Tertiary Clinical Centre - Lukas, Martin; Malickova, K; Kolar, M; Bortlik, M; Vasatko, M; Machkova, N; Hruba, V; Duricova, D; Lukas, Milan (Journal of Crohn's and colitis, 2020)
BACKGROUND AND AIMS: Patients' perspectives after switching from originator to biosimilar adalimumab have yet to be assessed. We evaluated the efficacy of switching from the originator adalimumab to a biosimilar compound [SB5] in patients with inflammatory bowel disease [IBD]. METHODS: Data on IBD patients who were switched from the originator to biosimilar adalimumab [SB5] at IBD Center ISCARE were analysed. Disease activity was assessed using standard clinical indices (Harvey-Bradshaw index [HBI] for Crohn's disease [CD] and partial Mayo score for ulcerative colitis [UC]), and laboratory parameters (C-reactive protein [CRP] and faecal calprotectin [FC]). Trough levels and anti-drug antibodies were measured. Patients were evaluated 10 weeks [W10] after the switch, and results were compared with the control group of patients on originator compound. RESULTS: A total of 93 patients switched to biosimilar adalimumab were included [CD 86%] and were matched to 93 controls for age, gender, diagnosis, and disease activity. There was no difference in the disease activity in either SWITCH or ORIGINATOR cohorts between Weeks 0 and 10. Similarly, no difference was found between cohorts at both prespecified time points. Moreover, no significant differences in CRP or FC concentrations were seen between W0 and W10 either in the SWITCH, or in the ORIGINATOR cohort [p >0.05]. Adalimumab serum trough levels remained stable after the switch. No new safety signals were detected. CONCLUSIONS: Our study confirmed that switching IBD patients from the originator adalimumab to a biosimilar compound [SB5] does not affect treatment efficacy.
Keywords: dospělí; Biosimilar Pharmaceuticals; Female; feces; Feces; C-Reactive Protein; Adult; výsledek terapie; ženské pohlaví; adalimumab; Tertiary Care Centers; lidé; centra terciární péče; Antibodies; Treatment Outcome; leukocytární L1-antigenní komplex; stupeň závažnosti nemoci; Colitis, Ulcerative; biosimilární léčivé přípravky; Adalimumab; retrospektivní studie; gastrointestinální látky; Crohn Disease; Male; Drug Substitution; ulcerózní kolitida; lidé středního věku; C-reaktivní protein; Crohnova nemoc; mužské pohlaví; náhrada léků; Gastrointestinal Agents; Leukocyte L1 Antigen Complex; Severity of Illness Index; Retrospective Studies; Middle Aged; protilátky; Humans